2020
DOI: 10.1007/s42452-020-2441-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining the polyphenol content, antioxidant activity and fatty acid composition of twenty-one different wastes of fruits, vegetables, oilseeds and beverages

Abstract: One of the most abundantly available, cost-effective valuable resources that are of all-time concern for minimization and economical re-utilization is food waste, and quantifying the phenolic compounds and identifying the principle chemical constituents will favour their industrial exploitation potential. Water, methanol and ethanol extracts of 21 common food wastes of four different classes (fruits, vegetables, oilseeds and beverages) were screened by determination of their antioxidant activity (measured by D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…Golden variety, finding a value of 34.39 ± 0.89 mg GAE/g d.m. Similarly, it is close to that reported by Kuppusamy et al [79] who carried out polyphenol extraction in pineapple peels using different solvents: water, methanol and ethanol, registering 68.3 ± 1.2, 28.6 ± 1.5 and 22.3 ± 0.6 mg GAE/g d.m, respectively. Lourenço et al [80] carried out the encapsulation of pineapple peel extracts that were obtained using a water: ethanol ratio (20:80 w/w), finding a TPC of 29.33 mg GAE/g d.m, value close to reported.…”
Section: Analysis Of the Control Sample With Respect To The Treatment...supporting
confidence: 90%
“…Golden variety, finding a value of 34.39 ± 0.89 mg GAE/g d.m. Similarly, it is close to that reported by Kuppusamy et al [79] who carried out polyphenol extraction in pineapple peels using different solvents: water, methanol and ethanol, registering 68.3 ± 1.2, 28.6 ± 1.5 and 22.3 ± 0.6 mg GAE/g d.m, respectively. Lourenço et al [80] carried out the encapsulation of pineapple peel extracts that were obtained using a water: ethanol ratio (20:80 w/w), finding a TPC of 29.33 mg GAE/g d.m, value close to reported.…”
Section: Analysis Of the Control Sample With Respect To The Treatment...supporting
confidence: 90%
“…Other studies with papaya residues also identified higher values for flavonoids compared to phenolic acids [ 55 , 61 ]. Vieira, Pinho, Ferreira and Delerue-Matos [ 37 ] analyzed different parts of chayote and observed a greater presence of flavonoids in the peel (approximately 2 times higher) compared to the pulp; a fact later confirmed by Kuppusamy et al [ 62 ], where FVB peels had higher amounts of flavonoids among twenty-one plant residues. It is also important to highlight that the class of other polyphenols (e.g., pyrogallol, 4-hydroxybenzaldehyde, vanillin) was the third most abundant class in all samples, and that lignans and stilbenes presented values close to 0%.…”
Section: Resultsmentioning
confidence: 82%
“…Recently, Kuppusamy et al (2020) observed the polyphenol content, antioxidant activity, and fatty acid profile of 21 different agro‐industrial wastes belonging to oilseed, beverages, fruits, and vegetables. They adapted different extraction solvents for extraction and probed different prominent antioxidant assays to estimate the phytonutrient capacity.…”
Section: Discussionmentioning
confidence: 99%